Computer simulated plant design for waste minimization/pollution prevention - Bumble, Stan (Lewis Publishers, 2000)
Environmental science combined with computer technology. One click on a mouse and information flows into your PC from up to 10,000 miles away. When you receive this information you can ferret through the data and use it in any number of computer programs. The result: solutions to plant design problems that affect the health and well being of people around the globe. What does that mean to you, the environmental professional, scientist, or engineer? Computer Simulated Plant Design for Waste Minimization/Pollution Prevention builds on the concepts introduced in Stan Bumble's Computer Generated Physical Properties, the first volume of the Computer Modeling for Environmental Management series. Bumble discusses using computer simulation programs to solve problems in plant design before they occur. He covers design issues for stationary and non-stationary sources of pollution, global warming, troposcopic ozone, and stratospheric ozone. With Computer Simulated Plant Design for Waste Minimization/Pollution Prevention you will understand how to use computer technology to design plants that generate little or no pollution. Even better, you can use the information generated by computer simulation for technical data in proposals, presentations and as the basis for making policy decisions.